Disaster preparedness for persons with disabilities in flood-prone areas of East Jakarta: A multidimensional environmental perspective - Melissa Aprilia; Rachmadi Purwana; Berton Panjaitan (Calamity: A Journal of Disaster Technology and Engineering, 2026)
Background: The increasing frequency and intensity of hydrometeorological disasters driven by climate change have heightened the vulnerability of persons with disabilities, particularly in urban flood-prone areas. Flooding is the most common disaster in Jakarta and disproportionately affects persons with disabilities due to barriers to accessing disaster information, evacuation routes, emergency shelters, and recovery resources. Although research on disaster preparedness among persons with disabilities has expanded, limited attention has been given to how environmental conditions shape preparedness. This study examines flood preparedness among persons with disabilities in flood-prone areas of East Jakarta through a multidimensional environmental perspective encompassing physical, social, and economic dimensions. Methods: This study employed a qualitative approach using in-depth interviews, focus group discussions (FGDs), observations, and document review. Data were collected from persons with disabilities, family members, community representatives, and local stakeholders and analyzed using thematic analysis. Findings: Disaster preparedness is shaped by the interaction of physical, social, and economic environments. Inaccessible evacuation routes, emergency shelters, and early warning systems constrain preparedness and response capacities. Social support from families, communities, and disability organizations facilitates access to information, evacuation, and emergency assistance, while limited economic resources reduce households’ capacity to prepare for, respond to, and recover from recurrent flooding. These dimensions are interconnected and collectively influence vulnerability and adaptive capacity. Conclusion: The study concludes that disaster preparedness among persons with disabilities is a multidimensional environmental phenomenon rather than solely an individual attribute. Novelty/Originality of this article: The novelty of this study lies in examining how the interactions among physical, social, and economic environmental dimensions shape disability-inclusive disaster preparedness in urban flood-prone communities.